Problematika Pendaftaran Tanah Wakaf di Kecamatan Berbek, Kabupaten Nganjuk: Analisis Kritis Perspektif Al-Qur’an - Ahmad Sulton Ariwibowo; Mohamad Zaenal Arifin; Moh. Safi'il Anam; Mohammad Muksi (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
This study examines the problems surrounding the registration of waqf land in Berbek District, Nganjuk Regency, through a critical analysis from the perspective of the Qur’an. The registration of waqf land functions as an instrument for legal certainty and the protection of waqf assets; however, in practice it continues to face various administrative and social obstacles. This research employs a qualitative method with a normative–empirical approach. Data were collected through interviews with officials of the Office of Religious Affairs (KUA), waqf nazhirs, and community leaders, and were supported by an analysis of waqf-related documents. The findings indicate that the main problems in waqf land registration in Berbek include the low level of legal awareness among wakifs and nazhirs, limited understanding of registration procedures, and the perception that a religious waqf pledge is sufficient without formal registration. From the Qur’anic perspective, these conditions contradict the values of trust (amānah), justice (‘adl), and the principle of documentation (al-kitābah), which aim to safeguard public interest (maṣlaḥah) and prevent disputes.